EFFECT OF CARDIAC ARREST MANAGEMENT TRAINING ON THE ABILITY OF ORDINARY PEOPLE TO PERFORM HIGH-QUALITY CARDIO PULMONARY RESUSCITATION - Meliana Nurvitasari; Janes Jainurakhma; Zulfikar Muhammad (Belitung Nursing Journal, 2020)
Background: The rate of cardiac arrest outside hospitals remains high in Indonesia. Performing Cardio Pulmonary Resuscitation (CPR) is advised as an emergency procedure to save a person’s life. However, lack of ordinary people is able to do CPR. Therefore, cardiac arrest management training is considered important to form a bystander in the community. Objective: This study aimed to determine if there is an effect of cardiac arrest management training on the ability of ordinary people to perform high-quality CPR. Methods: This study used one-group pretest-posttest design method with a total sample of 35 participants. Observation sheet based on American Heart Association was used to measure the ability to perform CPR. Paired-t test was used for data analysis. Results: There was a significant effect of the cardiac arrest management training on the ability to perform high-quality CPR (p<.001), with an increase of the mean value from 19.62 (SD=5.50) before intervention to 37.91 (SD=1.29) after intervention. Conclusion: The cardiac arrest management training at the community level is considered effective in increasing the ability to perform high-quality CPR. The findings of this study can be used as input for community nurses to provide pre-hospital management training specifically on cardiac emergency management training continually for ordinary people in order to help improve good prognosis and reduce mortality risk of out-of-hospital cardiac arrest.